Review of Maritime Transport 2010 - United Nations Conference on Trade; Development (United Nations, 2011)
More than 80 per cent of international trade in goods is carried by sea, and an even higher percentage of developing-country trade is carried in ships. This annual publication is an important source of information on this vital sector. It closely monitors developments affecting world seaborne trade, freight rates, ports, surface transport, and logistics services, as well as trends in ship ownership and control and fleet age, tonnage supply, and productivity. The Review contains a chapter on legal and regulatory developments and each year includes a chapter highlighting a different region. In 2010, the focus is on Asia and the Pacific.